"Birth is a miracle only to God": reconfiguring kinship through reproductive suffering in the South Sudanese diaspora. (3rd May 2016) - Jaysane-Darr, Anna
Abstract : Like many former refugee communities, South Sudanese in the United States are deeply invested in community fertility and the reproduction of the diaspora and the nation. For Dinka South Sudanese, ideas about fertility are typically intertwined with desire for the continuity of the patriline. In the diaspora, however, the affective and jural dimensions of parent–child kinship are being reconfigured in response to a range of factors. In this article, I examine reproductive suffering, defined as trauma suffered by women who experience reproductive complications in service to both the patriline and the nation, as one overlooked but important element that contributes to new kinship formations. Drawing on historical ethnographic literature from South Sudan and fieldwork with South Sudanese mothers and fathers in Massachusetts, I describe an emergent transformation of patrilineality in the diaspora community. I examine two cases of reproductive suffering – one of repeated foetal loss, the other maternal morbidity – that illuminate some of the key outcomes of this transformation, including a growing focus on maternal love, an increase in matrilateral kin claims and the increased relevance of a Christian God in mother–child relationships.